Proses Penyelesaian Perkara Jual Beli Hak AtasTanah Yang Dimiliki Lebih Dari Satu Orang(Studi Kasus Di Pengadilan Negeri Surakarta) - Sari, Nurdiana Novita; , Nuswardhani, SH., S.U (2016)
Happened a matter of buying and selling land that is performed more than one person where the plaintiff will do the breaking of land certificates but the defendant does not want to cede their land certificates. This research aims to know the status of ownership rights over the land owned by more than one person and the process of buying and selling rights to the land, to find out the judge's reasoning in determining proof and deciding the verdict on the matter of buying and selling land rights which owned by more than one person. This research method's used normative approaches which are descriptive. And the data used primary data and secondary data. The data collection techniques are used through the study of librarianship, documentation, a list of questions and interviews. The writer used qualitative data analysis. The results showed that the ownership status of land rights is belonging to the plaintiff and defendants, the process of buying and selling by the plaintiff and defendants, he was the judge looks at the process of proof in proceedings in the trial, the plaintiff can prove the evidence for the lawsuit, then a lawsuit plaintiff granted for entirely, defendants sentenced to submit certificate of land so that it can then be sold and the proceeds divided.